Superior loco-regional control after primary surgery compared to chemo-radiotherapy for advanced stage laryngeal cancer - Shelan, Mohamed; Anschuetz, Lukas; Schubert, Adrian; Bojaxhiu, Beat; Aebersold, Daniel M.; Elicin, Olgun; Giger, Roland (Frontiers in Oncology, 2023)
Objective The optimal strategy to treat loco-regionally advanced squamous cell carcinoma of the larynx (LSCC) remains to be defined. The goal of this single institution retrospective study was to report on oncologic outcome of advanced LSCC treated with curative intent. Methods Patients diagnosed and treated for stage T3-T4a LSCC between 2001 and 2014 were retrospectively analyzed. Time-to-event endpoints were calculated beginning from the date of histologic diagnosis, which were analyzed with log-rank test and Cox proportional hazard models. Results The cohort was divided into two subgroups: primary radiotherapy with concomitant cisplatin (CRT) (n=30, 38%) and primary surgery (n=48, 62%). Median follow-up was 56 months. Locoregional control (LRC) for the primary surgery and CRT were 95% and 50% in 5 years, respectively (p<0.01). Progression free survival (PFS) for the primary surgery and CRT were 61% and 38% in 5 years, respectively (p=0.23). The overall survival (OS) after primary surgery and CRT in 5 years were 63% vs. 65%, respectively (p=0.93). The 5-years LRC was significantly superior after surgery compared to RT for cT3 primaries (100% vs 50%, p= 0.0022). No significant differences were observed in the remaining subgroups regarding cT stage and PFS or OS. Conclusion Our series demonstrated superior LRC after primary surgery followed by risk-adapted adjuvant (C)RT compared to primary CRT in cT3 LSCC, but no significant difference in PFS or OS in locally-advanced LSCC. The optimal patient selection criteria for the ideal treatment for loco-regionally advanced LSCC still needs to be defined.